Densely functionalised spirocyclic oxetane-piperidine scaffolds for drug discovery - Geary, Gemma C.; Nortcliffe, Andrew; Pearce, Christopher A.; Hamza, Daniel; Jones, Geraint; Moody, Christopher J. (Elsevier, 2017)
A spirocyclic, sp3-atom rich oxetane-containing scaffold was synthesised in just two steps via a gold catalysed propargylic alcohol rearrangement. The key gold cyclisation can be undertaken on a 40 g scale allowing the preparation of 419 lead-like compounds based on the scaffold for the European Lead Factory.